2008
DOI: 10.1021/ja801927v
|View full text |Cite
|
Sign up to set email alerts
|

Two-Step Laser Mass Spectrometry of Asphaltenes

Abstract: Defined by their solubility in toluene and insolubility in n-heptane, asphaltenes are a highly aromatic, polydisperse mixture consisting of the heaviest and most polar fraction of crude oil. Although asphaltenes are critically important to the exploitation of conventional oil and are poised to rise in significance along with the exploitation of heavy oil, even as fundamental a quantity as their molecular weight distribution is unknown to within an order of magnitude. Laser desorption/ionization (LDI) mass spec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

17
249
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 176 publications
(266 citation statements)
references
References 25 publications
(38 reference statements)
17
249
0
Order By: Relevance
“…The soft ionization of petroleum molecules provided by ESI has been corroborated by good agreement of molecular weights measured by ESI with those measured by other soft ionization techniques such as two-step laser mass spectrometry (Hortal et al, 2007;Hortal et al, 2006;Pomerantz et al, 2008;Pomerantz et al, 2009;Rodgers and Marshall, 2007). ESI FT-ICR MS is useful for the analysis of complex mixtures because each elemental composition (C c H h N n O o S s ) has a unique molecular mass.…”
Section: Esi Ft-icr Msmentioning
confidence: 73%
“…The soft ionization of petroleum molecules provided by ESI has been corroborated by good agreement of molecular weights measured by ESI with those measured by other soft ionization techniques such as two-step laser mass spectrometry (Hortal et al, 2007;Hortal et al, 2006;Pomerantz et al, 2008;Pomerantz et al, 2009;Rodgers and Marshall, 2007). ESI FT-ICR MS is useful for the analysis of complex mixtures because each elemental composition (C c H h N n O o S s ) has a unique molecular mass.…”
Section: Esi Ft-icr Msmentioning
confidence: 73%
“…For instance Small-Angle X-ray and Neutron Scattering (SAXS and SANS) experiments were generally performed at concentrations close to 10 g.L -1 for asphaltenes dissolved in model solvents 17,18,[48][49][50][51] . It was not until 1999, using techniques such as fluorescence depolarization technique [52][53][54][55][56] , fluorescence correlation spectroscopy [57][58][59] and mass spectrometry 60,61 that reliable results, accounting for the molecular aggregation at higher concentrations, became available. These results have shown that typical mean molecular weights of asphaltenes were ∼750 g.mol -1 with a factor of 2 in the width of the molecular weight distribution.…”
Section: Structurementioning
confidence: 99%
“…Laser desorption/ionization mass spectrometry, although highly useful for biomolecule analysis, does not provide a reliable representation of petroleum components because of significant aggregation and fragmentation at the laser power required to generate a useful number of gas-phase ions (10). However, recent introduction of a two-color laser method (11), in which the first laser desorbs the neutrals and the second laser ionizes them, appears to overcome the disadvantages of single-color laser desorption/ ionization.…”
mentioning
confidence: 99%